Analisis Gaya Belajar terhadap Hasil Belajar Mahasiswa Angkatan Pertama Program Studi Pendidikan Biologi Universitas Tribhuwana Tunggadewi - Lathifah, Anis Samrotul; Fidiastuti, Hasminar Rachman (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2018)
The study program of Biology education in Unitri (University of Tribhuwana Tunggadewi, Malang) is a new study program, which has been operated for 1 year. Biology education has a vision that is a pioneer of biological educators who are based on cultured scientific as well as a center for the development of biology learning formed on multicultural and populist. To become a biology educator in accordance with the vision, the students are expected to understand the behavior or learning style to avoid the stress of learning that affects the continuity of the lecture. Students of Unitri who are mostly from Eastern Indonesia tend to be more vulnerable from learning stress since they have to adapt to different environments. Therefore, a research about student learning style analysis and its influence to learning result is conducted. De Porter and Hernacki divide learning styles into three types: visual, auditory, and kinesthetic learning styles. Based on the results of the learning style questionnaire given to 47 new students of biology education, 17% of students have visual learning style, 34% is auditory, and 49% is kinesthetic. To determine the effect on learning outcomes, the eta correlation test with significance value of learning result (score from the midterm test of cell biology course) is 0.086 bigger than Î± (0.05) which means there is no significant relationship between learning style of area with the score from the midterm test of cell biology course. This insignificant relationship can be influenced because students are new students who have not realized and understood their learning style. Hence, that special treatment is needed such as the existence of teaching materials or learning media that accommodate the learning style in order tp obtain significant results on the learning outcomes.